As artes visuais e a cultura popular no ensino médio: blocos tradicionais de São Luís do Maranhão e a valorização das identidades comunitárias - ARAUJO, Marilú Moraes (2020)
This research aims to demonstrate the strengthening of existing community identities in a Traditional Block through the study of popular culture in visual arts classes in high school. It belongs to the research line “Teaching, learning and creation processes in arts”, linked to the PROFARTES Master's Program. It was developed at the “Centro de Ensino São José Operário” (CESJO) in the years 2019/2020, through experiences and experiments that contributed to the students' aesthetic, critical and reflective development with regard to their artistic production and appreciation processes having by reference the Bloco Tradicional “Tropicais do Ritmo”. To achieve the proposed objectives, it is pertinent to know how the allegories, images and symbols of a Traditional Block can contribute to the knowledge about popular culture and community identities in high school visual arts classes. This work guides Barbosa (2010), Bakhtin (1987), Hall (2011), Hernández (2007), Rancière (2005), Bauman (2003), Canclini (1983), Ciampa (1984), Silva (2009), Moreira Neto (2016), Tinhorão (2006), among others. The methodological path is based on the participant-research method, with a qualitative approach, developed through research, lectures, visits and semi-structured interviews with people who are involved with the popular culture of Maranhão. The recording of everything was done through questionnaires, photos and videos, which gave rise to visual and documentary material on the community identities that work so that culture, and especially the Traditional Block, can happen, thus emphasizing the importance of these people for the preservation and valorization of popular culture in Maranhão. The result is presented through an exhibition of the works of CESJO students in the serigraph technique.